EFEKTIVITAS SENAM KAKI DIABETUS MELITUS TERHADAP STATUS SIRKULASI PERIFER PADA PASIEN DIABETUS MELITUS - S.Kep., Ns., M.Kes, Diyono,; , A.,M.Kes, Ratna Indriati (Politeknik Insan Husada Surakarta, 2015)
Background. The main factors that prompted researchers doing this study is because more and more patients diabetus mellitus (DM) with complications of leg ulcers and even some who have to be amputated fingers or toes. DM patients in Indonesia is predicted to rise further, so that the risk of foot ulcers will also be greater. Is a complication of diabetes foot ulcers due to neuropathy and angiopathy, which basically can be prevented with good foot care. This study sought to find or prove the effectiveness of DM leg exercises to improve peripheral circulation in patients diabetus mellitus.Objective: the purpose of this study was to assess the effectiveness of DM leg exercises to increase the status of the peripheral circulation in patients diabetus mellitus Method. This research is a Quasi Experiment with the design of one group pre test post test. The study population was patients with Diabetes Mellitus there Joho, Pracimantoro Wonogiri by 30 respondents. The sampling technique used is total sampling (sampling saturated). Data were analyzed using paired t test with SPSS for windows 16 series. Result. Women respondents were 19 (63.33%) and male respondents as many as 11 respondents (36.67%). Before the DM leg exercises, all respondents were 30 or 100% indicates the status of the peripheral circulation in grades 0-4 or bad category. Status peripheral circulation in diabetic patients after DM foot gymnastics in grades 0-4 (bad) as much as 4 respondents or 13.3%, while for grades 5-6 (good) by 26 or 86.7% .Value average peripheral circulatory status after DM foot gymnastics is 5.17 better than before performing leg exercises with value is 2,53Conclusion: Gymnastics feet DM is effective to improve the status of the peripheral circulation in diabetic patients with statistical test results Dependent paired t test (t test) obtained p value: 0.00 (p <0.05)Keywords: Gymnastics feet DM, peripheral circulation, Diabetus Mellitus